Cyclizations and fragmentations in the alkylation of 6‐chloro‐5‐hydroxy‐4‐aminopyrimidines with aminoalkyl chlorides. (10th February 2021) - Picazo, Edwige M. H.; Heptinstall, Amy B.; Wilson, David M.; Cano, Céline; Golding, Bernard T.; Waring, Michael J.
Abstract: Substituted aminopyrimidines are an important class of compounds, in part because they frequently show biological activity. Facile synthesis of polysubstituted aminopyrimidines is highly desirable for the synthesis of screening libraries. We describe a route to 4, 6‐diamino‐5‐alkoxypyrimidines via a SN Ar‐alkylation‐SN Ar sequence from readily available 4, 6‐dichloro‐5‐methoxypyrimidine, which allows the synthesis of such compounds with regiochemical control. The extension of this approach to alkylating agents bearing amino substituents led to unexpected and, in some cases, unprecedented products resulting from intramolecular SN Ar cyclization and subsequent fragmentation. Abstract :